DIFFERENTIATE LEARNING ACHIEVEMENT BY ETHNICITY IN SMAN 5 KUPANG - Hadrianus Jehanu; Marthen Tabun (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2024)
The aim of this research is to determine differences in student learning achievement based on ethnicity at SMA Negeri 5 Kupang. The approach used in this research is qualitative. The research subjects using purposive sampling technique consisted of school principals, teachers and students at SMA Negeri 5 Kupang. Research data was collected through interviews and documentation. This research data was analyzed using the interactive analysis technique of the Milles and Huberman model. This research found several findings. First, support factors from teachers, environmental factors, economic factors, cultural factors related to differences in student learning achievement based on ethnicity at SMA Negeri 5 Kupang have not been optimized properly and there are still several obstacles, namely from several ethnic groups at SMA Negeri 5 Kupang, like the ethnicities of Sumba, Timor, Rote, Sabu, Alor, Java, Sundanese, Timor Leste and Maluku, needs special attention from the school, considering that there are still many things that need to be paid attention to in terms of children's learning facilities such as books and the internet. , and other school supplies, support from teachers such as providing motivation, the school environment and attention from parents, the teacher's monotonous way of teaching to certain students, students' learning styles, social environmental factors inside the school and outside the school and Attention from the family needs to be increased.